Comportamiento Tribológico de Aluminio Sinterizado y Desgastado Bajo Distintas Condiciones - Fuentes Ramírez, Rosalba; Rubio Rosas, Efraín; Reyes Z., Veridiana; Castaño Meneses, Víctor Manuel (Acta Universitaria, 2003)
Wear is one of the most costly damages in industry and research has been directed towards its prevention. This paper deals with the behavior of aluminum pieces, prepared by powder metallurgy, under wear. The samples tested were prepared under different processing conditions (compacting pressure, temperature and sintering time). The wear test was carried out ina pin-in-disc machine, at various rates and wear pressures. The results showed the tribological behavior of aluminum. Also, a comparative study between a 356-aluminium alloy and pure aluminum was carried out, showing the feasibility of attaining similar tribological behavior between a conventional alloy and pure aluminum prepared by powder metallurgy techniques.